ISLAMIC EDUCATION IN THE TIME OF UMAR BIN KHATTAB: A HISTORICAL STUDY - Berlianto, Gesha; Putri, Yulita; Nurhuda, Abid (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Islamic education is required to be able to answer the challenges of every era. And the progress of this education started a long time ago when Islamic territory had reached from west to east, namely during the military expansion during the era of caliph Umar Bin Khattab. So the purpose of this study is to describe Islamic Education in the Era of Umar Bin Khattab. The method used is a literature study with descriptive techniques in concluding and analyzing the data so that this research is qualitative. The results of the study show that Islamic Education during the Umar Bin Khattab era included the provision of quality educational resources by sending them to become teachers and scholars in conquered countries. then the construction of educational infrastructure such as kuttab, majlis, and mosques. And finally, there are methods in education such as halaqah, talaqqi, and lectures.